2017
DOI: 10.18488/journal.8/2017.5.2/8.2.135.146
|View full text |Cite
|
Sign up to set email alerts
|

The Exports and Economic Growth Nexus in Cote D ivoire: Evidence from a Multivariate Time Series Analysis

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The existence of cointegrating vector implies the presence of long-run relationship between economic growth and clove exports in Zanzibar. These results coincide with results of Keho, (2017); and Ndubuisi (2012) who attested that exports can play a greater role in enhancing economic growth. The export of cloves is a vital source of foreign exchange, improves the balance of payments deficit and increases employment opportunities as well (Mohamed et al, 2012).…”
Section: Johansen Cointegration Testssupporting
confidence: 87%
“…The existence of cointegrating vector implies the presence of long-run relationship between economic growth and clove exports in Zanzibar. These results coincide with results of Keho, (2017); and Ndubuisi (2012) who attested that exports can play a greater role in enhancing economic growth. The export of cloves is a vital source of foreign exchange, improves the balance of payments deficit and increases employment opportunities as well (Mohamed et al, 2012).…”
Section: Johansen Cointegration Testssupporting
confidence: 87%
“…On the other hand, Keho (2017) used the ARDL model and Granger causality tests and found that there is a positive bi-directional causality relationship between domestic investment and economic growth in both the short and long run in the case of Cote D'Ivoire for the period 1965-2014. Adams et al (2017) used the ARDL Model and the results of the study revealed that domestic investment has a positive influence on Nigerian economic growth in the long run.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Increasing exports are important not only for developing but also developed economies, since the growth of export has forward and backward links to all sectors in the economy. Many countries have engaged in export promotion strategy far back in 1970 as part of the most proficient gears for growth and development because export has been regarded as a catalyst for the overall economic development (Amado & Mollo, 2015;Danylova & Kats, 2019;Keho, 2017). The ASEAN countries accounts for the 11 percent of world's agriculture output (see figure 1).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%